Human Lymphoid Histocultures - Introini, Andrea (Methods Mol Biol, 2018)
Human tissue explants provide a valuable tool for experimental studies of normal and pathological tissue physiology. They allow us to understand intercellular interactions by mirroring their original spatial relationship within body tissues, and can be employed to model host-pathogen interactions under controlled laboratory conditions. Here we describe a protocol to process and infect with human immunodeficiency virus (HIV) type 1 lymphoid tissue explants from human tonsils and maintain them in culture at the liquid-air interface in a non-polarized setting. These ex vivo-infected tissues have been successfully used to study the biology of early HIV-1 pathogenesis, as well as a platform to test the efficacy and toxicity of antiviral drugs.